Prevalence of psychosocial risks in the justice administration staff of the valencian community (Spain) - Gil-Monte, Pedro R. (2016)
The objective of the study was to evaluate the psychosocial factors in the work of the justice personnel of Valencia (Spain) to identify the prevalence of psychosocial risks. The participants were 402 workers (28.11 % men) including managers, processors, and social assistants. We assessed using the UNIPSICO questionnaire (includes demand factors, resource factors, and consequences of psychosocial risks). The main risks were work overload (46.02 % of participants in a high risk situation) within the demands; the lack of resources to carry out the work (76.37 % in a high risk situation); and the lack of autonomy (67.41 % in a high risk situation). For the consequences, 61.44 % of participants expressed labor dissatisfaction, and 27.11 % had to frequently consume drugs in the last year because of health problems arising from work. We conclude by recommending psychosocial intervention strategies to improve working conditions. DOI: https://doi.org/10.24265/liberabit.2016.v22n1.01